Genomic and phenotypic comparison between similar wine yeast strains of Saccharomyces cerevisiae from different geographic origins - Salinas, F. (2010)
Aims: To study genomic and phenotypic changes in wine yeasts produced in short time periods analysing yeast strains possibly derived from commercial strains recently dispersed. Methods and Results: We conducted a genomic and phenotypic comparison between the commercial yeast strain EC1118 and two novel strains (LV CB and L‐957) isolated from different wine areas industrially intervened <20 years ago. Molecular analysis by amplified fragment length polymorphism (AFLP) and RAPD‐PCR was not able to distinguish between these strains. However, comparative genomic hybridization (aCGH) showed discrete DNA gains and losses that allowed unequivocal identification of the strains. Furthermore, analysis of aCGH data supports the hypothesis that strains LV CB and L‐957 are derivatives from strain EC1118. Finally, scarce phenotypic differences in physiological and metabolic parameters were found among the strains. Conclusion: The wine yeasts have a very dynamic genome that accumulates changes in short time periods. These changes permit the unique genomic identification of the strains. Significance and Impact of the Study: This study permits the evaluation of microevolutive events in wine yeasts and its relationship with the phenotype in this species.